Measurement and Simulation Techniques for Piezoresistive Microcantilever Biosensor Applications - Aan Febriansyah; Ratno Nuryadi; Djoko Hartanto (Universitas Ahmad Dahlan, 2012)
Applications of microcantileversas biosensors have been explored by many researchers for the applications in medicine, biological, chemistry, and environmental monitoring. This research discusses a design of measurement method and simuations forpiezoresistivemicrocantileveras a biosensor, which consist of designing Wheatstone bridge circuit as object detector, simulation of resonance frequency shift based on Euler Bernoulli Beam equation, and microcantilever vibration simulation using COMSOL Multiphysics 3.5. The piezoresistivemicrocantilever used here is Seiko Instrument Technology (Japan) product with length of 110 μm, width of 50 μm, and thickness of 1 μm. Microcantilever mass is 12.815 ng, including the mass receptor. The sample object in this research is bacteria EColi. One bacteria mass is assumed to 0.3 pg. Simulation results show that the mass of one bacterium will cause the deflection of 0.03053 nm and resonance frequency value of 118.90 kHz. Moreover, four bacterium will cause the deflection of 0.03054 nm and resonance frequency value of 118.68 kHz. These data indicate that the increasing of the bacteria mass increases the deflection value and reduces the value of resonance frequency.